Periodontology New Insights - Sridharan, Gokul (Dentistry, 2023)
Periodontology is a specialized branch of dentistry that deals with the health and diseases of the periodontium, which is the supportive tissue surrounding the teeth. Periodontal diseases are common oral diseases that can affect the teeth and supporting structures, and maintaining a healthy periodontium is essential for preserving the integrity of dentition. Advances have been made in the pathophysiology, classification, diagnosis, and management of periodontal diseases over the years. This book aims to provide researchers and clinicians who deal with periodontal diseases with an overview of the latest insights regarding the periodontium and periodontal disease.